2018
DOI: 10.29252/ijrm.16.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone ameliorates some endocrine parameters and histological alteration in a rat model of polycystic ovary syndrome

Abstract: Background:Polycystic ovary syndrome (PCOS) is a common form of the endocrine disease which is associated with metabolic dysfunction. PCOS and type 2 diabetes mellitus are related in multiple aspects and are similar in many pathological features. Anti-diabetic effects of Nigella sativa and protective effects of it on reproductive system have been suggested in some reports.Objective:The aim of current study was to evaluate the effects of thymoquinone, the main components of Nigella sativa, on PCOS model of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Therefore, a new treatment strategy with less side effects, more affordable, and with more pleiotropic activity is required. Previous studies have documented the efficacy of several herbal medications such as resveratrol, 15 quercetin, 16 thymoquinone 17 and Ficus deltoidea 18 in restoring function of the ovaries, insulin sensitivity and hormonal profile in experimentally induced PCOS. These studies suggested that the herbal medicines with ovulatory and hypoglycemic effects might be considered as an alternative therapy for PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a new treatment strategy with less side effects, more affordable, and with more pleiotropic activity is required. Previous studies have documented the efficacy of several herbal medications such as resveratrol, 15 quercetin, 16 thymoquinone 17 and Ficus deltoidea 18 in restoring function of the ovaries, insulin sensitivity and hormonal profile in experimentally induced PCOS. These studies suggested that the herbal medicines with ovulatory and hypoglycemic effects might be considered as an alternative therapy for PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…A serious clinical complication that may result in polycystic ovary syndrome or increased estrogen levels is estradiol valerate-induced PCOS (47). Estradiol production is caused by the dominant follicle growing, and high estrogen levels indicate that FSH production will stop through a negative feedback system.…”
Section: Discussionmentioning
confidence: 99%
“…According to research by Taghvaee Javanshir et al, rats can develop PCOS when given estradiol valerate for 25 days. It can cause morphological changes, anovulation, metabolic problems, hormonal changes, and follicular cysts in the ovaries (47). Being overweight is frequently linked to PCOS and is a risk factor for developing other PCOS disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The number of follicular cysts decreased significantly with thymoquinone treatment along with an increase in the number of primary follicles, Graafian follicles, antral follicles, and corpus luteum. Thymoquinone treatment also reversed the elevated biochemical parameters, including plasma glucose, triglycerides (TGs), total cholesterol (TC), low-density lipoprotein-cholester-ol (LDL-c), high-density lipoprotein-cholesterol (HDL-c), LH, and FSH [35]. Moreover, an experimental study of letrozoleinduced PCOS female Sprague-Dawley rats revealed that N. sativa oil administration (5 and 10 mL/kg) for 7 weeks resulted in a significant increase in the number of rats undergoing regular cycles, the average number of regular cycles, the appearance of corpus luteum, and a decreased number of cystic follicles, along with a reduction of LH, testosterone, FSH, body weight, FBG, TC, LDL-c, TGs, and MDA.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Animal study (estradiol valerate-induced PCOS rats) [35] • Significant improvements in ovarian morphology, ovarian function, and ovulation similar to metformin. • Significant reduction of number of follicular cysts along with an increase in number of primary follicles, antral follicles, Graafian follicles and corpus luteum.…”
mentioning
confidence: 99%